2022
DOI: 10.1007/s10845-022-02026-8
|View full text |Cite
|
Sign up to set email alerts
|

Investigation and machine learning-based prediction of parametric effects of single point incremental forming on pillow effect and wall profile of AlMn1Mg1 aluminum alloy sheets

Abstract: Today the topic of incremental sheet forming (ISF) is one of the most active areas of sheet metal forming research. ISF can be an essential alternative to conventional sheet forming for prototypes or non-mass products. Single point incremental forming (SPIF) is one of the most innovative and widely used fields in ISF with the potential to form sheet products. The formed components by SPIF lack geometric accuracy, which is one of the obstacles that prevents SPIF from being adopted as a sheet forming process in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 65 publications
0
6
0
Order By: Relevance
“…The coefficient of determination R 2 value was determined according to the following relationship (Najm & Paniti, 2023):…”
Section: Resultsmentioning
confidence: 99%
“…The coefficient of determination R 2 value was determined according to the following relationship (Najm & Paniti, 2023):…”
Section: Resultsmentioning
confidence: 99%
“…Economical, technological and ecological aspects of SPIF versus conventional deep drawing were presented by Petek et al [16] and Oleksik et al [17]. The disadvantage of the SPIF process is the relatively large springback of the components after the forming process [18] and the pillow effect [19]. Behera and Ou [20] found that the stress-relieving heat treatment of titanium sheets affects the dimensional accuracy of parts formed using SPIF.…”
Section: Introductionmentioning
confidence: 99%
“…Recently, researchers are focusing on the application of machine learning (ML) techniques for predicting several process specific dimensions [3]. These include forming accuracy [4], surface quality [5], tool load [6], forming temperature [7], the pillow effect [8] and the material flow curve [9]. Due to the lack of industrial ISF production lines, the data used for training the ML models has to be gathered by the research institutes themselves.…”
Section: Introductionmentioning
confidence: 99%